Isolation and characterization of the mink interferon-epsilon gene and its antiviral activity - Zhang, Hailing; Zhang, Dongliang; Zhang, Shasha; Liu, Hao; Wang, Han; Wang, Cong; Zou, Deying; Hu, Bo; Lian, Shizhen; Lu, Shiying; Bai, Xue (Frontiers in Veterinary Science, 2023)
Interferon (IFN) is a cytokine secreted by a variety of cells and has a broad spectrum of antiviral and immunoregulatory effects. IFN response is the first line of defense against viral invasion and thus plays a central role in the regulation of the immune response. IFN-epsilon (IFN-ε) is a newly discovered type I IFN, which, unlike other type I IFNs, does not require viral induction. IFN-ε is constitutively expressed in epithelial cells and plays an important role in mucosal immunity. In this study, we evaluated the biological activity of the mink interferon (MiIFN)-ε gene in prokaryotic cells. Quantitative reverse transcription-polymerase chain reaction (qRT-PCR) was used to evaluate the expression of IFN-ε in different mink tissues. MiIFN-ε was highly expressed in brain, lung, tracheal, kidney, intestinal, bladder, ovary, and testis tissues. There was no significant difference in MiIFN-ε expression between female and male minks except in the reproductive system. The expression of the small ubiquitin-like modifier (SUMO3)-MiIFN-ε fusion gene was induced by isopropylβ-d-thiogalactoside, and MiIFN-ε was collected after SUMO-specific protease digestion. We tested the antiviral activity of MiIFN-ε against vesicular stomatitis virus (VSV) in Feline kidney 81 (F81) epithelial cells. We used qRT-PCR to analyze the expression of several IFN-stimulated genes (ISGs), including ISG15, 2ʹ-5ʹ oligoadenylate synthetase (2ʹ-5ʹOAS1), and myxovirus resistance protein 1 (Mx1). Recombinant IFN-ε induced high expression of ISGs in F81 cells. Compared with those in the A group, the expressions of ISG15 and Mx1 in C and D were significantly increased, and the differences were extremely significant (p < 0.0001). IFN-ε indirectly played an antiviral role. These findings lay the foundation for a detailed investigation of IFN-ε in the future.